Pembaharuan Pendidikan Islam dalam Bangunan Sistem Pendidikan Nasional - Muhammad Abrar Parinduri; Zuliana Zuliana (UMSU, 2021)
The presence of modernization in the world of Islamic education seems to be a necessity that cannot be avoided. The birth of reformer figures in the Islamic world who came from the Middle East and Indonesia became a separate impetus to accelerate the pace of renewal of Islamic education. This research uses library research type (library research) which is carried out using literature (literature) in the form of books, notes, and research reports from previous research. Sources of data can be obtained from documents or document studies. Document study, namely looking for data about things or variables in the form of notes or transcripts, books, newspapers, magazines, and other documents needed for research data. This research proves that the flow of renewal in Islamic education finds momentum when the Indonesian government is able to synergize with Muslim figures. Likewise, the accommodative and cooperative attitude displayed by some Indonesian Muslim leaders and Islamic community organizations has contributed to the government's belief that advancing Islamic educational institutions is not something that is scary but will add stability to the condition of government and politics in Indonesia. It is at this stage that the reform of Islamic education is ultimately integrated into the national education system.